Latarjet Procedure for the Treatment of Anterior Glenohumeral Instability in the Athlete – Key Considerations for Rehabilitation - Helen Bradley; Lucca Lacheta; Brandon T. Goldenberg; Samuel I. Rosenberg; Matthew T. Provencher; Peter J. Millett (International Journal of Sports Physical Therapy)
The Latarjet procedure with transfer of the coracoid process and its attached conjoint tendon is a well-established surgical technique for the treatment of anterior glenohumeral instability in patients with anteroinferior bone loss and/or high risk for recurrence. Biomechanical and clinical studies have shown excellent results and high rates of return to sports. However, there is an absence of standardized, objective criteria to accurately assess an athlete’s ability to progress through each phase of rehabilitation. Return to sports rehabilitation, progressed by quantitatively measured functional goals, may improve the athlete’s integration back to sports participation. Therefore, the purpose of this clinical commentary is to provide a rehabilitation protocol for the Latarjet procedure, progressing through clearly defined phases, with guidance for safe and effective return to sport. Recommended criteria are highlighted which allows the clinician to progress the patient through each phase appropriately rather than purely following timeframes from surgery. This progression ensures the patient has completed a thorough rehabilitation program that addresses ROM, strength, power, neuromuscular control and a graded return to play.